Analisis Model Peningkatan Mutu Pendidikan melalui Pembelajaran Berbasis Online - Safwan, Safwan; Syarifah Rahmah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
Online-based learning at SDIT Al Mukhlisin has not been able to improve the quality of education and to describe the model of improving the quality of education through online-based learning at SDIT Al Mukhlisin, the research method used is qualitative, the results show that online-based learning in terms of improving the quality of education is only limited to What Group Apps. Resources cannot be increased through online-based learning at SDIT Al Muklisin due to the limited use of the Integrated Quality Management and Management information system application at SDIT Al Mukhlisin using the school website, online-based learning, compiling learning plans every semester of the academic year, whose final stages are in the form of softcopy and hardcopy.